Pencucian Uang di Negara-Negara APEC: Analisis Model Gravitasi tentang Daya Tarik dan Pilihan Tujuan - Ariesiyani, Amarillys Enika Noora; Alham, Lalu Garin (AML/CFT Journal : The Journal Of Anti Money Laundering And Countering The Financing Of Terrorism, 2023)
This paper has three main contributions. First it attempts to measure which APEC countries are attractive destinations for money laundering to Indonesia. Second it measures and ranks the degree of money laundering attractiveness in-between APEC country members themselves. Third, it tests the variables contributing to a country’s money laundering attractiveness. The attractiveness is measured using the Gravity model derived from Newtonian gravitational equations by utilizing variables ranging from countries’ wealth, government attitude on money laundering, corruption perception index, SWIFT membership, conflict, financial secrecy, and physical & cultural distances. Pearson correlation analysis is also employed to test the statistical interaction & correlation between corresponding variables. Our simulations show that several countries consistently sit on the top 3 (three) most attractive money laundering destinations: Singapore, Hongkong, and the United States. It is also found that financial secrecy and GNI per capita significantly correlate with the degree of money laundering attractiveness. This analysis unveils that an attractive financial regime (beneficial ownership and bank secrecy) and a strong economy attract money launderers to conceal their ill-gotten money in a country.